Tubulin modulating antifungal and antiproliferative pyrazinone derivatives. Issue 3 (1st February 2016) - Taggi, Andrew E.; Stevenson, Thomas M.; Bereznak, James F.; Sharpe, Paula L.; Gutteridge, Steven; Forman, Robert; Bisaha, John J.; Cordova, Daniel; Crompton, Martina; Geist, Lora; Kovacs, Patrick; Marshall, Eric; et al.
Graphical abstract: Abstract: A novel class of synthetic tubulin polymerization disruptors, based on a substituted pyrazin-2-one core, has been discovered. These molecules have proven to be potent broad spectrum fungicides, with activity on agriculturally important ascomycete and basidiomycete pathogens. They have also been found to be particularly potent against human rhabdomyosarcoma cells. Using an efficient synthetic route, the agricultural and medicinal activity was explored.